Disk and Envelope Streamers of the GGD 27-MM1 Massive Protostar - Fernandez Lopez, Manuel (2023)
We present new Atacama Large Millimeter/submillimeter Array 0.98 mm observations of the continuum emission and several molecular lines toward the high-mass protostellar system GGD 27-MM1, driving the HH 80-81 radio jet. The detailed analysis of the continuum and the CH3CN molecular emission allows us to separate the contributions from the dust content of the disk (extending up to 190 au), the molecular content of the disk (extending from 140–360 au), and the content of the envelope, revealing the presence of several possible accretion streamers (also seen in other molecular tracers, such as CH3OH). We analyze the physical properties of the system, producing temperature and column density maps, and radial profiles for the disk and the envelope. We qualitatively reproduce the trajectories and line-of-sight velocities of the possible streamers using a theoretical model approach. An ad hoc model of a flared disk comprising a hot dust disk embedded in cold gas fits the H2S emission, which revealed the molecular disk as a crescent shape with a prominent central absorption. Another fit to the central absorption spectrum suggests that the absorption is probably caused by different external cold layers from the envelope or the accretion streamers. Finally, the analysis of the rotation pattern of the different molecular transitions in the molecular disk suggests that there is an inner zone devoid of molecular content.